2010
DOI: 10.1111/j.1349-7006.2009.01427.x
|View full text |Cite
|
Sign up to set email alerts
|

Myristoylated alanine‐rich C kinase substrate phosphorylation promotes cholangiocarcinoma cell migration and metastasis via the protein kinase C‐dependent pathway

Abstract: Myristoylated alanine-rich C kinase substrate (MARCKS), a substrate of protein kinase C (PKC) has been suggested to be implicated in cell adhesion, secretion, and motility through the regulation of the actin cytoskeletal structure. The quantitative real-time-polymerase chain reaction analysis revealed that MARCKS is significantly overexpressed in Opisthorchis viverriniassociated cholangiocarcinoma (CCA) (P = 0.001) in a hamster model, which correlated with the results of mRNA in situ hybridization. An immunohi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 38 publications
3
49
0
Order By: Relevance
“…This is because MARCKS expression is ubiquitous in various normal and tumor tissues. Despite this, there is a consensus that phospho-MARCKS, a post-translational modification, is associated with cell motility, and has a role in the regulation of cancer cell invasiveness and metastasis (2,4,14,15). Of note, our laboratory discovered that inhibition of MARCKS phosphorylation was able to reduce lung cancer metastasis in murine models (2).…”
Section: To the Editormentioning
confidence: 99%
“…This is because MARCKS expression is ubiquitous in various normal and tumor tissues. Despite this, there is a consensus that phospho-MARCKS, a post-translational modification, is associated with cell motility, and has a role in the regulation of cancer cell invasiveness and metastasis (2,4,14,15). Of note, our laboratory discovered that inhibition of MARCKS phosphorylation was able to reduce lung cancer metastasis in murine models (2).…”
Section: To the Editormentioning
confidence: 99%
“…MARCKS is a well‐established regulator of migration in multiple cell types. Dysregulation of MARCKS is closely associated with metastasis in a wide range of cancers and is an indicator of poor prognosis 19, 20. MARCKS increases cell motility through the protein kinase B pathway in fibroblasts21 and glial cells 22.…”
Section: Introductionmentioning
confidence: 99%
“…The data confirms the hypothesis that phosphorylated MARCKS was overexpressed during lung cancer. To support the data, it was reported that the phosphorylated MARCKS specifically regulate the cancer migration and metastasis (Chen et al, 2014;Chen and Rotenberg, 2010;Ghoul et al, 2006;Reddy et al, 2010;Techasen et al, 2010).…”
Section: Discussionmentioning
confidence: 68%
“…At the same time it was also identified that in lungs, MARCKS especially phosphorylated MARCKS, plays a crucial role in controlling mucin secretion and inflammation (Eckert et al, 2010;Green et al, 2011;Li et al, 2001;Park et al, 2007;Singer et al, 2004). In addition, it was reported that phosphorylated MARCKS specifically regulate the cancer migration and metastasis (Chen et al, 2014;Chen and Rotenberg, 2010;Ghoul et al, 2006;Reddy et al, 2010;Techasen et al, 2010). In contrast, very little is known about the importance of phospho-MARCKS and its relevance in lung cancer.…”
Section: Introductionmentioning
confidence: 97%